Pain‐autonomic interaction: A surrogate marker of central sensitization. (22nd September 2020) - Scheuren, Paulina S.; Rosner, Jan; Curt, Armin; Hubli, Michèle
Abstract: Background: Central sensitization represents a key pathophysiological mechanism underlying the development of neuropathic pain, often manifested clinically as mechanical allodynia and hyperalgesia. Adopting a mechanism‐based treatment approach relies highly on the ability to assess the presence of central sensitization. The aim of the study was to investigate potential pain‐autonomic readouts to operationalize experimentally induced central sensitization in the area of secondary hyperalgesia. Methods: Pinprick evoked potentials (PEPs) and sympathetic skin responses (SSRs) were recorded in 20 healthy individuals. Three blocks of PEP and SSR recordings were performed before and after heat‐induced secondary hyperalgesia. All measurements were also performed before and after a control condition. Multivariate analyses were performed using linear mixed‐effect regression models to examine the effect of experimentally induced central sensitization on PEP and SSR parameters (i.e. amplitudes, latencies and habituation) and on pinprick pain ratings. Results: The noxious heat stimulation induced robust mechanical hyperalgesia with a significant increase in PEP and SSR amplitudes ( p < 0.001) in the area of secondary hyperalgesia. Furthermore, PEP and SSR habituation were reduced ( p < 0.001) after experimentally induced central sensitization. Conclusions: The findings demonstrate that combined recordings of PEPs and SSRs are sensitive to objectify experimentally induced central sensitization and may have a great potential to reveal its presence in clinical pain conditions. Corroborating current pain phenotyping with pain‐autonomic markers has the potential to unravel central sensitization along the nociceptive neuraxis and might provide a framework for mechanistically founded therapies. Significance: Our findings provide evidence that combined recordings of sympathetic skin responses (SSRs) and pinprick evoked potentials (PEPs) might be able to unmask central sensitization induced through a well‐established experimental pain model in healthy individuals. As such, these novel readouts of central sensitization might attain new insights towards complementing clinical pain phenotyping.